KOMITMEN ORGANISASI PADA GURU SD NEGERI UPTD PENDIDIKAN WIRADESA KABUPATEN PEKALONGAN - Karniti -; tukijan - (JURNAL EKONOMI MANAJEMEN AKUNTANSI, 2013)
The aim this research analyzes work motivation influence  and organization culture towards organization commitment with job satisfaction as intervening variable. Population entire teachers at  state  elementryschool  upt official education  wiradesa pekalongan as much as 174 person and sample that taken as much as 154 person with use purposive sampling. Analyzer that used in this research path analysis. Hypothesis testing result shows that work motivation  influence towards job  satisfaction,  influential organization culture  towards job satisfaction, positive influential job satisfaction towards performance teacher,  positive influential work motivation towards organization commitment. Path analysis result shows that work motivation positive influential towards organization commitment with job satisfaction as intervening variable, Organization culture positive towards organization commitment with job  satisfaction as intervening variable Keyword: work motivation, organization culture, work satisfaction, organization commitment